TINGKAT KEPUASAN KONSUMEN TERHADAP E-SERVICES PEMASARAN ONLINE MAKANAN OLAHAN AYAM MELALUI E-COMMERCE (STUDI KASUS PADA AYIPS BANDAR LAMPUNG) - Putri Larasati; Ktut Murniati; Maya Riantini (Politeknik Negeri Lampung, 2021)
Since Ayips pioneering the business, Ayips has been doing marketing online by using Instagram, Whatsapp, GoFood and GrabFood to aim to introduce the product to consumers more widely and quickly. To achieve the goal, Ayips has to fulfill the expectations of its consumers by electronic services also known as e-services. The research aims to analyze e-services performance in the online marketing of chicken Ayips by e-commerce to fulfill the expectation of its costumers. Ayips Bandar Lampung was chosen purposely. The samples used in this study were 75 people. The data was analyzed using the Importance Performance Analysis (IPA). The results showed that Ayips' willingness to answer questions and help customers if they have trouble dealing online needs improvement.